OPTIMIZATION OF THE ANTENNA TECHNIQUE TO INCREASE THE RELIABILITY AND STABILITY OF THE GPS SIGNAL IN COMPLICATED CONDITIONS - PLISH, VOLODYMYR; ANDRUHIV, TARAS (Herald of Khmelnytskyi National University. Technical sciences, 2025)
This article explores the critical challenges of maintaining reliable and stable GPS signal reception in complex environments such as urban landscapes, mountainous terrains, and areas with high interference levels. It emphasizes the design, optimization, and implementation of microstrip antennas with circular polarization to enhance the reliability and stability of GPS signals. Addressing issues such as signal reflections from structures and terrain, the study proposes an innovative approach to antenna design that incorporates compact dimensions, efficient signal reception, and advanced polarization techniques. The research integrates theoretical modeling with experimental validation, employing finite element methods to analyze key parameters such as gain, directivity, and standing wave ratios. The experimental tests conducted under variable environmental conditions demonstrate the proposed antenna’s capacity to isolate unwanted signals, maintain consistent performance, and significantly enhance signal stability. Special attention is given to the implications of this technology for unmanned aerial vehicles (UAVs) and other mobile platforms, where lightweight and compact antennas are essential for minimizing aerodynamic impact and optimizing performance. By achieving effective circular polarization through innovative feeding mechanisms and phase adjustments, the study demonstrates how the proposed antenna design improves the overall efficiency of GPS-based navigation systems. The article further discusses the comparative analysis of antenna design methodologies and provides insights into the integration of the proposed solutions with modern satellite navigation technologies. It highlights the practical benefits of implementing advanced antenna systems in transport, logistics, and autonomous systems, emphasizing their critical role in enhancing the accuracy and reliability of navigation. Future research directions include expanding the frequency band compatibility of the proposed antenna and its integration with alternative satellite systems to broaden its applicability. The findings of this research contribute to the ongoing development of robust and efficient navigation technologies, particularly for environments with challenging conditions, paving the way for more reliable and versatile GPS applications.